In defence of a logic for 'because'. Issue 2 (2nd April 2016) - Schnieder, B.
Abstract : The present author developed a calculus for the logic of 'because'. In a recent paper in this journal, it has been claimed that the central inference rules for the logic are invalid and that the intuition upon which the rules are based is not accounted for. This note criticises these arguments and presents an independent argument in favour of the rules used in the logic.